‛Other Books Like Rebecca? Are There Any?’: The Singular Fate of a Novel - Xavier Lachazette (Maison de la Recherche en Sciences Humaines, 2021)
Daphne Du Maurier’s international bestseller, Rebecca, has always puzzled readers, reviewers, and critics alike. Often hard put to define why the novel has them in its thrall and what genre or category it can be said to fall under, they resort to explanations which are both numerically impressive and strikingly contradictory. To underline the exceptional singularity of such a work, the unique literary and historical status of Du Maurier’s fifth novel will first be analysed. Du Maurier’s surprisingly unperceptive assessment of her own work will then be studied, both before its publication and after it became a runaway bestseller. Finally, we will have a look at some of the critical attention it has recently received, in the press and in academic articles, to show that assessing or categorising Rebecca has always been a contentious issue, not just for its author but also for critics at large.